Digitalisasi UMKM dan Peningkatan Daya Saing di Pasar Global - Rahmat Hidayat (Economics Note, 2025)
The rapid development of digital technology has transformed business ecosystems worldwide, particularly for Micro, Small, and Medium Enterprises (MSMEs). In the global market, digitalization serves as a key driver for enhancing competitiveness, efficiency, and market access. This study aims to analyze the impact of digital transformation on MSMEs’ competitiveness in the global market. The research applied a mixed-method approach combining survey data from 250 MSMEs in Indonesia with secondary data from international trade reports. The results indicate that digital adoption significantly improves marketing reach, operational efficiency, and innovation capability. However, challenges remain in terms of digital literacy, infrastructure, and regulatory support. The discussion highlights the importance of integrated policies, digital skills training, and financial inclusion to optimize the benefits of digitalization. The findings suggest that digital transformation not only enhances MSMEs’ resilience but also positions them as competitive players in global value chains. This study contributes to the growing literature on digital economy and provides policy recommendations for governments, business associations, and entrepreneurs to foster inclusive and sustainable digital growth.